Samuela Twardowskiego Dafnis: małżeństwo – retoryka – prefeminizm Sceny XIII - Obremski, Krzysztof (Śląskie Studia Polonistyczne, 2016)
In 1638 dramatic idyll a male view of marriage is undermined by the voice of these women (Dafnis appears here as pars pro toto) who critically perceived a marital status as a life determined by abandoning the virtue of chastity. In Scene 13 one can already recognize – at least on a verbal level – the equal rights: Peneus’s male arguments are juxtaposed with Dafnis’s female ones. The nymph – in a prefeminist way? – juxtaposes her female subjectivity with male objectification in favour of the values which for Apollo and Peneus can be imagined at most: love for a woman and the continuity of a family (exalted by being related to a god).